Aging‐related Alzheimer's disease‐like neuropathology and functional decline in captive vervet monkeys (Chlorocebus aethiops sabaeus). Issue 11 (5th April 2021) - Frye, Brett M.; Craft, Suzanne; Latimer, Caitlin S.; Keene, C. Dirk; Montine, Thomas J.; Register, Thomas C.; Orr, Miranda E.; Kavanagh, Kylie; Macauley, Shannon L.; Shively, Carol A.
Abstract: Age‐related neurodegeneration characteristic of late‐onset Alzheimer's disease (LOAD) begins in middle age, well before symptoms. Translational models to identify modifiable risk factors are needed to understand etiology and identify therapeutic targets. Here, we outline the evidence supporting the vervet monkey ( Chlorocebus aethiops sabaeus ) as a model of aging‐related AD‐like neuropathology and associated phenotypes including cognitive function, physical function, glucose handling, intestinal physiology, and CSF, blood, and neuroimaging biomarkers. This review provides the most comprehensive multisystem description of aging in vervets to date. This review synthesizes a large body of evidence that suggests that aging vervets exhibit a coordinated suite of traits consistent with early AD and provide a powerful, naturally occurring model for LOAD. Notably, relationships are identified between AD‐like neuropathology and modifiable risk factors. Gaps in knowledge and key limitations are provided to shape future studies to illuminate mechanisms underlying divergent neurocognitive aging trajectories and to develop interventions that increase resilience to aging‐associated chronic disease, particularly, LOAD. Abstract : The vervet model of Alzheimer's disease‐like neuropathology and related behavioral and physiological characteristics. Research Highlights: Aging vervets exhibit a suite of traits consistent with early Alzheimer's disease (AD) and provide a powerful, naturally occurring model for AD. This comprehensive characterization of vervet monkeys provides the foundation for future studies of modifiable factors that increase risk or resilience to AD.